Infra-Red Gas Analysers of Liquid Crystal Type for Environmental Monitoring - V. I. Nazarov; E. V. Nazarova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals an opportunity to use infra-red gas analysers on the basis of the developed dichroic liquid crystal cells for investigation of absorption bands of various gases in the near infrared spectral region.